Energy consumption, CO2 emissions and GDP in Nigeria - Chindo, Sulaiman; Abdul Samad, Abdul Rahim; Waziri, Salisu Ibrahim; Huong, Wong M.; Ahmad, Abdulfatah Abubakar (Springer, 2015)
This paper investigated the relationship between energy consumption, carbon dioxide (CO2) emissions and GDP in Nigeria using autoregressive distributed lag approach to cointegration. The empirical results revealed that there is a long run relationship energy consumption, CO2 emissions and GDP. Both in the long run and short run, CO2 emissions has been found to have a significant positive impact on GDP, meaning that an increase in CO2 emissions facilitates GDP growth. On the other hand, energy consumption shows significant negative impact on GDP in the short run. We therefore, suggested that renewable source of energy such as solar and wind could be explored and considered as an alternative source of energy since Nigeria is well endowed with solar energy. This will assist in reducing CO2 emissions and at the same time sustaining long run growth in GDP.